Novel Strategies for Preventing Fungal Infections—Outline - Claire Price (Pathogens, 2025)
Fungal infections are a significant global health challenge, causing approximately 3.8 million deaths annually, with immunocompromised populations particularly at risk. Traditional antifungal therapies, including azoles, echinocandins, and polyenes, face limitations due to rising antifungal resistance, toxicity, and inadequate treatment options. This review explores innovative strategies for preventing and managing fungal infections, such as vaccines, antifungal peptides, nanotechnology, probiotics, and immunotherapy. Vaccines offer promising avenues for long-term protection, despite difficulties in their development due to fungal complexity and immune evasion mechanisms. Antifungal peptides provide a novel class of agents with broad-spectrum activity and reduced resistance risk, whilst nanotechnology enables targeted, effective drug delivery systems. Probiotics show potential in preventing fungal infections, particularly vulvovaginal candidiasis, by maintaining microbial balance. Immunotherapy leverages immune system modulation to enhance antifungal defenses, and omics technologies deliver comprehensive insights into fungal biology, paving the way for novel therapeutic and vaccine targets. While these approaches hold immense promise, challenges such as cost, accessibility, and translational barriers remain. A coordinated effort among researchers, clinicians, and policymakers is critical to advancing these strategies and addressing the global burden of fungal infections effectively.